1907 Ariz. Sess. Laws 15 - (:unkn) unknown (My University, 1907)
An Act to Prohibit Officers from Carrying Firearms While Under the Influence of Liquor and for Other Purposes, ch. 16, § 1: Prohibited law enforcement from carrying a pistol, gun, or other firearm while intoxicated. Also prohibited striking any person with a pistol, gun, or other firearm while an officer is intoxicated.
Keywords: PEACE OFFICERS